2012
DOI: 10.1002/masy.201251113
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assisted Extrusion of Polyamide 6 Nanocomposites Based on Carbon Banotubes

Abstract: Summary: Polyamide 6 (PA6)/multiwall carbon nanotubes (MWCNTs) nanocomposites have been prepared by an extrusion process assisted by ultrasounds. The ultrasounds system has been incorporated at the extrusion die, when the material is flowing through the exit channel. The application of an ultrasound field to a polymer melt has been shown a very efficient method to improve productivity of the process. When ultrasounds are applied, the extrudate flow is highly enhanced maintaining the same processing conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…All the samples were prepared using the same experimental conditions: temperature profile (270 °C to 300 °C at the die), screw speed between 100 and 175 rpm, torque between 60 and 80 Nm and pressure between 80 and 85 bar. The screw profile was designed to achieve a high to medium shear profile that was optimised in previous studies [ 58 , 59 ]. A screw diameter of 25 mm and a length/diameter ratio of 40 were used in the different test procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the samples were prepared using the same experimental conditions: temperature profile (270 °C to 300 °C at the die), screw speed between 100 and 175 rpm, torque between 60 and 80 Nm and pressure between 80 and 85 bar. The screw profile was designed to achieve a high to medium shear profile that was optimised in previous studies [ 58 , 59 ]. A screw diameter of 25 mm and a length/diameter ratio of 40 were used in the different test procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The optimum level of additive dispersion into the polymeric matrix was determined using an ultrasonic device specially designed for this purpose, fully described in previous studies [ 58 , 59 ]. These studies varied the concentration of nanoadditives and the extrusion conditions in PA6 matrices.…”
Section: Methodsmentioning
confidence: 99%
“…The observed effect is attributed to the fact that the ultrasound breaks the agglomerates of MWCNT improving its dispersion, which affects to a greater degree the rheology of the material than to the electrical conductivity [30]. Blanco et al [53] mention that ultrasonic vibration has a significant effect on the conductivity of PA/MWCNT systems; in these nanocomposites, the percolation rate is reduced from 7 to 3 wt% when ultrasound is applied. This is attributed to a better dispersion of nanotubes in the matrix, resulting in an increase of three orders of magnitude in the electrical resistivity for the system PA6/MWCNT at 7 wt%.…”
Section: Polymer Nanocomposite Focus Of the Study Property Improvemenmentioning
confidence: 99%
“…This is attributed to a better dispersion of nanotubes in the matrix, resulting in an increase of three orders of magnitude in the electrical resistivity for the system PA6/MWCNT at 7 wt%. These authors concluded that the application of ultrasound improves the processability of the material and that it is possible to reduce the percentage of nanotubes in the preparation of nanocomposites with conductive properties without affecting thermal properties [53]. Ávila-Orta et al [51] used polypropylenes with different flow rates (MFI) and 10% multiwall carbon nanotubes for the preparation of nanocomposites.…”
Section: Polymer Nanocomposite Focus Of the Study Property Improvemenmentioning
confidence: 99%
“…22 Proper distribution and orientation is not easily obtained due to graphene nanoplatelets (GnPs') large surface area, van der Waals forces (which hold the sheets together), 23 and low solubility in organic solvents and polymer melts, 23 resulting in low levels of dispersion and exfoliation when using conventional manufacturing processes like solution or melt blending. 24 Many advanced techniques have shown excellent levels of dispersion including ultrasound-assisted extrusion, 25 addition of surfactants 26 or functionalized groups, 17 water, 27 or supercritical CO 2 , 28 and in situ polymerization. 29 Melt mixing or melt compounding is a process in which a polymer and filler are compounded together in a high shear environment, 18 conventionally done in an extruder.…”
Section: ■ Introductionmentioning
confidence: 99%